2010
DOI: 10.1186/1476-7120-8-21
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of pulmonary vascular resistance in pulmonary arterial hypertension

Abstract: BackgroundEchocardiographic ratio of peak tricuspid regurgitant velocity to the right ventricular outflow tract time-velocity integral (TRV/TVI rvot) was presented as a reliable non-invasive method of estimating pulmonary vascular resistance (PVR). Studies using this technique in patients with moderate to high PVR are scarce. Left ventricular outflow tract time-velocity integral (TVI lvot) can be easier to measure than TVI rvot, especially in patients with severe pulmonary hypertension (PH) with significant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 11 publications
(24 reference statements)
2
32
2
Order By: Relevance
“…One study reported no benefit to using LVOT over RVOT-VTI. 10 In addition, CO is the product of stroke volume and heart rate. Integrating heart rate into the equation did not improve estimates.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported no benefit to using LVOT over RVOT-VTI. 10 In addition, CO is the product of stroke volume and heart rate. Integrating heart rate into the equation did not improve estimates.…”
Section: Discussionmentioning
confidence: 99%
“…RVOT systolic excursion ¼ RVOT end-diastolic diameterÀRVOT end-systolic diameter RVOT end-diastolic diameter Pulmonary vascular resistance (PVR) was calculated using the following formula: 21,24 PVR =Peak tricuspid regurgitation velocity /RVOT velocity time integral ratio Quantitative assessment of the RV was obtained by measuring the end-diastolic RV area on the apical four-chamber image. A ratio of end-diastolic RV area to end-diastolic LV diameter ratio was then expressed as previously described.…”
Section: Methods: Study Groupmentioning
confidence: 99%
“…The sample volume was placed so that the closing but not opening click of the pulmonary valve was visualized. 22,23 Pulsed-wave Doppler was used rather than continuous-wave Doppler to eliminate cases with increased pulmonary velocities secondary to either pulmonary valve or peripheral pulmonary artery stenosis and assess more accurately the duration of the signal. 14,22 Velocity time integral values were obtained by tracing the RVOT spectral pulsed Doppler signals, as previously described.…”
Section: Echocardiographic Examinationmentioning
confidence: 99%